2007
DOI: 10.1039/b617823e
|View full text |Cite
|
Sign up to set email alerts
|

Tandem C–C coupling – intramolecular acetylenic Schmidt reaction under Pd/C–Cu catalysis

Abstract: A new one-pot reaction for the regioselective construction of a six-membered fused N-heterocyclic ring leading to isoquinolones under Pd/C-Cu catalysis is described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(17 citation statements)
references
References 26 publications
0
17
0
Order By: Relevance
“…73 Notably, the reaction of terminal alkynes with organic azides in the presence of transition-metal catalysts afforded 1,4-disubstituted 1,2,3-triazoles. This methodology has shown remarkable applications in organic synthesis, 74 and an intramolecular version of this [3+2] cycloaddition to afford isoindoline fused with triazoles has also been reported.…”
Section: Palladium/carbon In the Union Of Organic Azide And Terminal mentioning
confidence: 99%
See 1 more Smart Citation
“…73 Notably, the reaction of terminal alkynes with organic azides in the presence of transition-metal catalysts afforded 1,4-disubstituted 1,2,3-triazoles. This methodology has shown remarkable applications in organic synthesis, 74 and an intramolecular version of this [3+2] cycloaddition to afford isoindoline fused with triazoles has also been reported.…”
Section: Palladium/carbon In the Union Of Organic Azide And Terminal mentioning
confidence: 99%
“…Because of their utility as inhibitors of thymidylate synthase (TS) for the potential treatment of cancer, a number of 3-substituted isoquinolone derivatives 47 were prepared by the reaction of 2-iodobenzoyl azides 46 with terminal alkynes under palladium/carbon-copper catalysis (Table 25). 73 Notably, the reaction of terminal alkynes with organic azides in the presence of transition-metal catalysts afforded 1,4-disubstituted 1,2,3-triazoles. This methodology has shown remarkable applications in organic synthesis, 74 and an intramolecular version of this [3+2] cycloaddition to afford isoindoline fused with triazoles has also been reported.…”
Section: Palladium/carbon In the Union Of Organic Azide And Terminal Alkynesmentioning
confidence: 99%
“…The coupling process proceeded smoothly when acetonitrile was chosen as the solvent in the presence of Et 3 N, 10% Pd/C, PPh 3 , and CuI (a ratio of 1:4:2) at 80 • C. Further studies showed that the Et 3 N-Pd/C-PPh 3 -CuI catalytic system was efficient in Sonogashira reactions. Pal and co-workers applied the Sonogashira coupling protocol to the synthesis of isoquinolones 119 (Scheme 22) [58]. The coupling reaction between 2-iodobenzoylazides 117 and terminal alkynes 118, followed by an intramolecular Schmidt reaction, afforded corresponding target products in moderate to excellent yields.…”
Section: Sonogashira Coupling Reactionmentioning
confidence: 99%
“…Treatment of ortho-iodobenzoyl azides with terminal alkynes in the presence of Pd/C, PPh 3 , and CuI in EtOH at 80 • C under N 2 afforded 3-substituted isoquinolones as the major products [114]. The formation of isoquinolones is proposed involving in situ generation of ortho-alkynyl benzoyl azides via Pd/C-mediated Sonogashira coupling followed by intramolecular acetylenic Schmidt reaction with denitrogenation (Scheme 29).…”
Section: Isoquinolone Syntheses Via Intramolecular Annulation Reactionsmentioning
confidence: 99%